Peran Jejaring Kolaborasi Dalam Meningkatkan Kinerja Pemasaran Umkm Dimoderasi Oleh Peran Pemerintah Di Wilayah Perbatasan Kalimantan Barat - Novri, Beni (Publikasi Indonesia, 2025)
This study aims to analyze the role of collaborative networks in improving the marketing performance of MSMEs moderated by the government’s role in the border region of West Kalimantan. Methodology: The research employs a qualitative approach with a case study design. Primary data were collected through in-depth interviews with 30 MSME actors in the border areas of West Kalimantan (Sambas, Sanggau, and Kapuas Hulu Regencies) and 5 relevant government officials. Secondary data were obtained from policy documents, statistical reports, and scientific literature. Data analysis was performed using a thematic approach with the assistance of Nvivo 12 software. Findings: The research found that: (1) Collaborative networks positively influence the marketing performance of MSMEs in border areas through three main mechanisms: market access, knowledge transfer, and value chain efficiency; (2) The government’s role moderates this relationship through facilitative policies, capacity development programs, and trade infrastructure development; (3) Border region-specific challenges such as infrastructure gaps and regulatory differences require adaptive collaborative network models. Practical Implications: This study provides guidance for MSMEs in building effective collaborative networks by considering structural, relational, and cognitive dimensions. For the government, this research offers policy recommendations to strengthen its moderating role in supporting MSME collaborative networks in border regions. Originality: This research contributes new insights on the dynamics of collaborative networks in border regions by integrating Resource-Based View, Dynamic Capabilities, and Network Theory, and developing a conceptual model that explains the government’s moderating role in the relationship between collaborative networks and MSME marketing performance.